INOVASI PEMBELAJARAN BERBASIS MASALAH BERBANTUAN MEDIA TRANSVISI UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - Rahayu, Indah Puji; Yulianingsih, Utari; Septiani, Dwi; Wijaya, Angga Adistia (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This study aims to design problem based learning with transvisi media. The learning was applied to improve science process skills at electrolyte-nonelectrolyte material and concepts redox. Quasi experiment design with pretest-posttest control group was used. The differences between pre and post test of Science Process Skill was assumed as effect of treatment. Research subjects were two classgroup of X class in SMA N 1 Randublatung. Â One class was as control group and the other was as experiment group. They were determined through cluster random sampling. Science process skill was measured by multiple choice test-with reason. Data were analyzed by t-test. Results showed that the implementation of problem based learning at electrolyte-nonelectrolyte and redox can improve studentsâ science process skills, as well as students gave positive responce to learning implementation.Â Keywords: Science Process Skills; Transvisi Media; PBL Model.